RF31 Adverse childhood experiences or adverse socio-economic conditions? assessing impacts on adolescent mental health in the UK millennium cohort study. (September 2018) - Straatmann, VS; Whitehead, M; Taylor-Robinson, DC
Abstract : Background: Maltreatment in childhood is associated with subsequent adverse health outcomes, but more recently the concept of 'adverse childhood experiences' (ACEs) has gaining increasing policy traction. Various adverse childhood exposures and risk conditions have been termed ACEs and have been associated with poor subsequent health outcomes, particularly mental health, but less consideration has been given to the interplay of these factors with childhood socio-economic circumstances (SECs). We aimed to explore the social patterning of ACEs, and the extent to which ACEs explain the association of SECs and adolescent mental health. Methods: We used data from the U.K. Millennium Cohort Study based on 6748 children (9 months, 3, 5, and 14 years' old sweeps). The outcome was adolescent mental health at age 14 (Total Difficulties Score of the Strengths and Difficulties Questionnaire;>17 score borderline-abnormal); poverty was used as a measure of SEC at birth (Income <60% average). ACEs were scored through 7 factors (verbal and physical maltreatment; parental drug use [age 5]; maternal domestic violence, parental divorce, maternal mental illness, and alcohol abuse [age 3 or 5]), and we generated a binary definition of exposure to 4 or more ACEs (yes/no). Counterfactual mediation analysis was used to estimate the total effect of SECs on odds of mental health problems (MHP) at age 14; and to assess the proportion mediated through exposure to multiple ACEs, using the paramed function in STATA. Results: 8.4% were exposed to multiple ACEs by age 5% and 12.6% of adolescents had MHP at age 14. Adolescent MHP and exposure to ACEs were more common among those growing up in low vs high SECs, respectively (8.3%[7.4–9.2] vs 18.8%[16.9–20.9]); 10%[8.2–12.1] vs 7.9%[7.0–8.9)]. Exposure to ACEs was associated with an increased odds of MHP (OR2.2 [1.5–3.0]). The total effect of low SECs on adolescent MHP was OR 1.9 (1.5–2.3). Overall 8% of the total effect of SEC on odds of MHP was mediated through exposure to ACEs. Conclusion: The increased risk of MHP in U.K. adolescents growing up in disadvantaged SECs is partly explained by exposure to ACEs. Children growing up in disadvantaged SECs are more at risk of experiencing multiple ACEs, and from a policy perspective it is important to separate modifiable childhood SECs from harmful exposures. Efforts to decrease inequalities in adolescents MHP should focus on reducing modifiable socio-economic inequalities; and early identification and targeted intervention for children that have experienced ACEs. The self-reported outcome is a limitation of this study.